2007
DOI: 10.1124/jpet.106.116640
|View full text |Cite
|
Sign up to set email alerts
|

STI-571 (Imatinib Mesylate) Enhances the Apoptotic Efficacy of Pyrrolo-1,5-Benzoxazepine-6, a Novel Microtubule-Targeting Agent, in Both STI-571-Sensitive and -Resistant Bcr-Abl-Positive Human Chronic Myeloid Leukemia Cells

Abstract: Interactions between the Bcr-Abl kinase inhibitor STI-571 (imatinib mesylate) and a novel microtubule-targeting agent (MTA), pyrrolo-1,5-benzoxazepine (PBOX)-6, were investigated in STI-571-sensitive and -resistant human chronic myeloid leukemia (CML) cells. Cotreatment of PBOX-6 with STI-571 induced significantly more apoptosis in Bcr-Abl-positive CML cell lines (K562 and LAMA-84) than either drug alone (P Ͻ 0.01). Cell cycle analysis of propidium iodide-stained cells showed that STI-571 significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…The expression of Bcl-2 family membersFupstream regulators of apoptogenic mitochondrial proteins releaseFwas examined. As previously reported in primary CML cells or other Bcr-Abl-overexpressing cell lines, [25][26][27][28] imatinib treatment was associated with downregulation of both cytoprotective Bcl-xL and Mcl-1 but not Bcl-2 and increased expression of the pro-apoptotic Bcl-2 member Bim in LAMA84/Neo cells. Noteworthy, these effects were remarkably inhibited in LAMA84/SphK1 cells (Figure 2f).…”
Section: Sphk1 Overexpression Inhibits Imatinib-induced Apoptosis In supporting
confidence: 56%
See 1 more Smart Citation
“…The expression of Bcl-2 family membersFupstream regulators of apoptogenic mitochondrial proteins releaseFwas examined. As previously reported in primary CML cells or other Bcr-Abl-overexpressing cell lines, [25][26][27][28] imatinib treatment was associated with downregulation of both cytoprotective Bcl-xL and Mcl-1 but not Bcl-2 and increased expression of the pro-apoptotic Bcl-2 member Bim in LAMA84/Neo cells. Noteworthy, these effects were remarkably inhibited in LAMA84/SphK1 cells (Figure 2f).…”
Section: Sphk1 Overexpression Inhibits Imatinib-induced Apoptosis In supporting
confidence: 56%
“…30 Herein, we establish that SphK1 overexpression can interfere with the expression of Bcl-2 family members known to be downstream effectors of imatinib. [25][26][27][28] On the one hand, imatinib-induced Bcl-xL and Mcl-1 downregulation was inhibited by SphK1 overexpression. On the other hand, the pro-apoptotic Bcl-2 member Bim upregulation induced by imatinib was inhibited by SphK1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…The PBOX compounds also induced apoptosis in primary CML samples including those resistant to imatinib. In addition we have shown that the PBOXs enhance the apoptotic efficacy of imatinib in CML cell lines (Bright et al, 2009;Greene et al, 2007). Furthermore we have demonstrated the in vivo efficacy of a representative pro-apoptotic PBOX compound, PBOX-6, in a CML mouse model of the T315I Bcr-Abl mutant.…”
Section: Apoptosis Modulatorsmentioning
confidence: 89%
“…There were indications that CML cells could have a dysfunctional mitotic checkpoint, as their resistance to spindle poisons was reported previously. In the K562 and Lama-84 CML cell lines, microtubule disruption caused either by paclitaxel, nocodazole or novel microtubule-targeting agent PBOX-6 led to polyploidization without the presence of significant apoptosis (Greene et al, 2007). Imatinib treatment minimized the formation of polyploid cells and enhanced the apoptotic index upon treatment of CML cells with spindle poisons.…”
Section: Mitotic Checkpoint Failurementioning
confidence: 99%